Iron Deficiency Parameters in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder - Percinel, Ipek; Yazici, Kemal Utku; Ustundag, Bilal (Springer, 2016)
The aim of this study is to compare iron deficiency parameters in patients with stimulant-naive attention-deficit/hyperactivity disorder (ADHD) and healthy controls, to investigate whether there are differences among the ADHD presentations, and to evaluate the relationship between ADHD symptom severity and serum ferritin levels. In addition, ADHD-Predominantly Inattentive (ADHD-PI) patients with restrictive hyperactivity/impulsivity symptoms were evaluated as a separate group with restrictive inattention presentation (ADHD-Rest) and were compared with other groups. Patients with ADHD-Rest are typically defined as having six or more symptoms of inattention and fewer than three symptoms of hyperactivity/impulsivity. A total of 200 ADHD cases consisting of 100 ADHD-Combine (ADHD-C) and 100 ADHD-PI and a total of 100 healthy control cases were included in the study. The Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version was performed in a semi-structured interview during the diagnosis. The Turgay DSM-IV-Based Child and Adolescent Behavior Disorders Screening and Rating Scale, the Conners' Rating Scale-Revised: Long Form (Parent-Teacher) (CPRSR:L, CTRS-R:L) were used for clinical evaluation. Hemogram, serum iron, iron binding capacity and serum ferritin levels were assessed. There were no significant differences between the ADHD patients and the healthy control cases in terms of iron deficiency parameters. Further, there were no significant differences among the ADHD presentations in terms of the same parameters, nor were there any significant differences when the groups were examined after the identification of the ADHD-Rest. The CPRS-R:L Hyperactivity and the CTRS-R:L Hyperactivity scores were negatively correlated with serum ferritin level in the ADHD group. To our knowledge, our current study is the first to compare serum ferritin levels in ADHD-Rest with other presentations of ADHD, and included the largest number of patients that were classified by ADHD presentations. Elucidation of these findings is important for both the etiology and treatment of ADHD.
Keywords: Adolescent; Attention deficit hyperactivity disorder; Children; Ferritin; Iron